Human eye-inspired soft optoelectronic device using high-density MoS2-graphene curved image sensor array - Changsoon Choi (Nature Portfolio, 2017)
Soft and flexible optoelectronic devices may provide effective routes toward retinal implants for enhanced visual functions. Here, the authors fabricate a curved array of flexible MoS2-graphene photodetectors and demonstrate its potential application as ophthalmic imaging element in mouse models.